2011
DOI: 10.17221/345/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tungsten on growth, biochemical constituents, molybdenum and tungsten contents in wheat

Abstract: The effect of various concentrations (3, 9, 27, 81, and 243 mg/kg) of tungsten (W) on growth performance, biochemical constituents and tungsten and molybdenum (Mo) contents in wheat was observed. Lower doses (up to 9 mg/kg) of tungsten showed promotory effects whereas higher doses retarded. An increment in growth, biomass, chlorophyll and carbohydrate contents was observed. Tungsten contents in root and shoot showed a very strong linear dependence on the soil applied W contents. Mo contents in plant tissue sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…At the tungsten concentrations used in this experiment, no differences in biomass production were found between the control and tungsten enriched soils. The results are in agreement with previous findings for another species, Triticum aestivum, which reported that biomass was not influenced by low tungsten concentrations in soil [34,35]. A reduction in biomass production was discovered in soils only with very high tungsten concentrations of up to 5000 mg kg −1 for Glycine max [30] and 2600 mg kg −1 for Helianthus annuus [26].…”
Section: Biomass Productionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the tungsten concentrations used in this experiment, no differences in biomass production were found between the control and tungsten enriched soils. The results are in agreement with previous findings for another species, Triticum aestivum, which reported that biomass was not influenced by low tungsten concentrations in soil [34,35]. A reduction in biomass production was discovered in soils only with very high tungsten concentrations of up to 5000 mg kg −1 for Glycine max [30] and 2600 mg kg −1 for Helianthus annuus [26].…”
Section: Biomass Productionsupporting
confidence: 92%
“…There are few studies on tungsten uptake by plants and the reported tungsten concentrations in plants are highly variable due to the differences between plant species and experimental conditions [26,30,34]. Although in hydroponic experiments, the tungsten uptake can be directly linked to the concentration of metal in solution and to specific tolerance mechanisms, the interpretation of the phytoavailability in soil is more complex since it is essentially determined by tungsten species in the soil liquid phase.…”
Section: Influence Of Soil Characteristics On Plant Uptakementioning
confidence: 99%
“…Several previous studies observed the dependence of plant W content on the soil W contents [3], [18], [28][30]. Previous experiments in field showed W contents in the roots and leaves of maize were significantly correlated with the W content in the soil adjacent to an old tungsten mine (Pechtelsgrün) in Germany [18].…”
Section: Resultsmentioning
confidence: 97%
“…This order is similar to that for wild Calluna Vulgaris , Taraxacum officinale , and Trifolium pretense reported by Wilson and Pyatt [15] and Jiang et al [18] , i.e., W content in root > W content in leaf > W content in stem. In addition, content and enrichment in the root of Sunflowers, Ryegrass(Lolium perenne), Nothofagus menziesii , wheat , and cowpea growing in W-spiked soils were also higher than those in their leaves [2] , [12] , [20] , [28] , [29] . The common range of W in terrestrial plants was <0.001 to 0.15 mg kg −1 [6] .…”
Section: Resultsmentioning
confidence: 99%
“…W is uptaken by the roots and translocated to the upper plant organs via the xylem. W accumulation in the root tissues is much higher than in the shoot [ 4 , 34 , 35 ]. Anthocyanins may also facilitate W accumulation in some plant species [ 36 ].…”
Section: W Effects On Plantsmentioning
confidence: 99%